CSR in mission statements of Polish chemical industry companies (content analysis results) - Bortnowska, Hanna; Seiler, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
Due to the specific nature of their activities, chemical companies are exposed to significant reputational risk. One way to reduce this risk is by implementing a CSR policy. CSR can be built into the company`s strategy and communicated as a mission statement. The purpose of the article was to determine: 1. the types of values which chemical industry companies in Poland display in their mission statements, 2. if chemical industry companies in Poland display CSR values in their mission statements, 3. if these companies differ from others operating in the chemical sector in Poland in terms of displaying CSR in mission statements.
Keywords: chemical industry; CSR; mission statement; values